Osthole Increases the Sensitivity of Liver Cancer to Sorafenib by Inhibiting Cholesterol Metabolism. (26th November 2022) - Fan, Ke; Huang, Hui; Zhao, Ying; Xie, Tao; Zhu, Zeng-Yan; Xie, Mei-Lin
Abstract: Osthole is a natural product that has an inhibitory effect on liver cancer, but its effect on the sensitivity of liver cancer to sorafenib is poorly understood. Here, we investigated the effect of osthole and possible sensitization mechanisms. Our results showed that the combination of 2.5 μM sorafenib and 10 μM osthole had significantly synergistic inhibitory effects on proliferation, colony formation, and migration of HCCLM3, sorafenib-resistant HCCLM3 (HCCLM3-SR), and SK-Hep-1 cells. After treatment of HCCLM3 cells-inoculated subcutaneous xenotransplanted tumor mice with 100 mg/kg osthole, 70 mg/kg sorafenib or their combination for 24 day, the tumor volume, tumor weight, and tumor weight coefficient were significantly lower in the osthole + sorafenib group than in the sorafenib group. Compared with the control group, the total cholesterol and low density lipoprotein-cholesterol contents in serum and tumor tissue were significantly decreased in the osthole or osthole + sorafenib groups, the sterol regulatory element binding protein (SREBP)-2c, 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR), and low-density lipoprotein receptor (LDLR) protein expressions in tumor tissue were significantly downregulated as well. In conclusion, osthole can increase the sensitivity of liver cancer to sorafenib, and the mechanism is related to the downregulations of SREBP-2c, HMGCR, and LDLR protein expressions and subsequent inhibition of cholesterol metabolism.